The Philippines' voluntary national review on the sustainable development goals - Celia M. Reyes; Jose Ramon G. Albert; Aubrey D. Tabuga; Arkin A. Arboneda; Jana Flor V. Vizmanos; Carlos C. Cabaero (Philippine Institute for Development Studies (PIDS), 2019)
United Nations member-states, including the Philippines, committed to the 2030 Agenda for Sustainable Development and the Sustainable Development Goals (SDGs) to "conduct regular and inclusive reviews of progress at the national and sub-national levels, which are country-led and country-driven". The Voluntary National Review (VNR) aims to facilitate the sharing of experiences, including successes, challenges, and lessons learned, to accelerate the implementation of the 2030 Agenda. The VNR also seeks to strengthen policies and institutions of governments and to mobilize multi-stakeholder support and partnerships for the implementation of the SDGs. In particular, this VNR report examines where the country stands in several SDGs, analyzing baseline data and recent historical data on SDG indicators, as well as other supporting indicators and identifying challenges and constraints. With the theme, "Empowering people and ensuring inclusiveness and equality", the following set of goals were reviewed in depth in this report: SDG 4 (quality education), SDG 8 (decent work and economic growth), SDG 10 (reduced inequalities), SDG 13 (climate action), SDG 16 (peace, justice and strong institutions), and SDG 17 (partnerships).
Keywords: 330; Sustainable Development Goals; Voluntary National Review; quality education; decent work and economic growth; reduced inequalities; climate action; peace; justice and strong institutions; partnerships